2014
DOI: 10.1016/j.jcte.2014.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of hospitalized diabetic foot patients in a multi-disciplinary team setting: Thailand's experience

Abstract: AimsThe aims of this study were to evaluate the outcomes of treatment among hospitalized patients with diabetic foot ulcers, the risk factors for non-healing ulcers, and the rate of major amputation among Thai patients.MethodsA retrospective study of hospitalized diabetic foot patients treated at Theptarin Hospital during the period of 2009–2013. The complete healing rate was assessed at 12 months after admission.ResultsDuring the study period, 232 patients (123 males and 109 females) with 262 admissions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…The associated comorbidities detected in our patients were slightly lower than in the study in Thailand, which reported nephropathy in up to 44.4 % of patients [48]. Comorbidities such as hypertension, dyslipidemia, and chronic kidney diseases may influence outcome when they are present as most of these are associated with atherosclerosis and cause impaired endothelial function.…”
Section: Discussioncontrasting
confidence: 70%
“…The associated comorbidities detected in our patients were slightly lower than in the study in Thailand, which reported nephropathy in up to 44.4 % of patients [48]. Comorbidities such as hypertension, dyslipidemia, and chronic kidney diseases may influence outcome when they are present as most of these are associated with atherosclerosis and cause impaired endothelial function.…”
Section: Discussioncontrasting
confidence: 70%
“…DFU is the most frequent cause of hospitalization among diabetic patients and LEA is the most feared consequence of foot ulceration ( 2 , 3 , 7 ). The present study examined whether or not certain baseline characteristics and laboratory measures can predict the risk of LEA.…”
Section: Discussionmentioning
confidence: 99%
“…Our hospital was considered as the main referral medical center in Central Java District, thus hospitalized patients contained complexities and more advanced DFU with an increased risk of extensive surgical management. This fact becomes a relatively common scenario in developing countries while there was a sequential timeline of patients before referred to the hospital and brings considerable delay for optimal management when an amputation surgery was inevitable ( 3 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although diabetic ulcers should ideally be managed by a multidisciplinary healthcare team (Thewjitcharoen et al, 2014), the primary responsibility is with the nurses globally (Fourie, 2013). Optimum knowledge and positive attitudes of nurses are necessary for best practice on diabetic ulcer care (Gagliardino et al, 2007).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%